Recent Advances in Photocatalytic Transformation of Carbohydrates Into Valuable Platform Chemicals - Chen, Huan; Wan, Kun; Zheng, Fangjuan; Zhang, Zhuo; Zhang, Hongyu; Zhang, Yayun; Long, Donghui (Frontiers in Chemical Engineering, 2021)
In response to the less accessible fossil resources and deteriorating environmental problems, catalytic conversion of the renewable lignocellulosic biomass to replace fossil resources for the production of value-added chemicals and fuels is of great importance and has attract broad interest from a growing scientific community. Carbohydrate, including cellulose and hemicellulose, constitute more than 60% of lignocellulosic biomass and represent the most abundant source of renewable carbon in nature. Depolymerization of carbohydrate and its derivatives can obtain a series of valuable platform chemicals. Photocatalytic transformations of lignocellulose using sustainable solar energy have been identified as a promising strategy and attracted much attention. This review is aimed to provide an overview of the up-to-date contributions achieved in the selective photocatalytic transformation of carbohydrate and its derivatives. We then put forward future perspective and challenges in this field.